Social enterprising observance among B40 urban women for socioeconomic sustainability - Rokis, Rohaiza (European Center of Sustainable Development, 2019)
This article explores the enterprising capabilities of economically challenged women in the urban city of Kuala Lumpur, Malaysia. The study assumes that entrepreneurial awareness and entrepreneurial intention are good predictors of women who are socioeconomically sustainable. The study sample comprises the B40 women in Kuala Lumpur, Malaysia. The B40 group refers to the "bottom 40 percent" members of the population, with a monthly household income of RM3,855 and below (USD945 and below). A total of 404 B40 urban women are drawn from a clustered random sample of four so-called "poor" municipal residents in Kuala Lumpur. A questionnaire survey is used to study their levels of entrepreneurial awareness and intention, administered via the Statistical Package for the Social Sciences (SPSS) Version 22. The data are analysed using descriptive statistics, ANOVA and Pearson Correlation. The findings indicate a significant relationship between their levels of entrepreneurial awareness and entrepreneurial intention with being socioeconomically sustainable. Four important indicators are deduced: 1) upholding economic justice for B40 urban women; 2) reducing urban poverty concentration among women; 3) innovating new working avenues for women homemakers in the informal work sector; and 4) enhancing moral responsibility towards sustaining the natural environment. Based on these empirical outcomes, the research also recommends a suitable approach to social entrepreneurship among women of different ethnic groups. Significantly, it will contribute to the pursuit of community development and national unity.